Elective open bedside tracheostomy in the neurosurgical intensive care unit - Maharjan, Niran; Shrestha, Sangeeta; Bhattarai, Binod; Cherian, Iype (Journal of College of Medical Sciences-Nepal, 2015)
JCMS Background and Objectives: Tracheostomy is electively performed in critically ill patients requiring prolonged respiratory support. The risk of transporting, the increasing associated cost and operative room schedule are some of the obstacles for wider acceptance of this procedure. The use of rigid selection criteria exclude many patients who would benefit of this approach. The present study was designed to determine the safety of open bedside tracheostomy (OBT) as a routine intensive care units (ICU) procedure without any selection criteria, considering its peri and postoperative complications. Materials & Methods: Retrospective medical chart review of all patients that underwent elective tracheostomy between June 2014 and January 2015. Results: The study group comprised 52 patients with a mean age of 40.4±15.1 years. The incidence of intra-procedure complications was 5.7% and post-procedure complications was 3.8%. Conclusions: Open bedside tracheostomy seems to be a safe and simple procedure, even when performed by a trained resident under controlled circumstances, and should be considered as an option for ICU patients. JCMS Nepal. 2015;11(1): 9-11